Development and validation of a Chinese insulin medication literacy scale for patients with diabetes mellitus - Si, Fangying; Feng, Tao; Shi, Xiangfen; Chen, Sufang (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to develop a simplified insulin medication literacy scale for patients with diabetes mellitus in China (Ch-InMLS), assess the level of insulin medication literacy, and evaluate its psychometric properties.MethodsWe developed an initial scale based on the framework of the knowledge–attitude–practice model (KAP), with “skills” added. The items were developed from literature review and insulin-related guidelines, semi-structured interviews, and face validity. After two rounds of expert consultation and a pilot survey, a final version of the scale was developed. A cross-sectional survey was conducted with 553 patients with diabetes mellitus in Zhengzhou for psychometric evaluation. In the construct validity analysis, the number of participants was 262 for exploratory factor analysis and 291 for confirmatory factor analysis. In the reliability analysis, internal consistency reliability and split-half reliability were evaluated using Cronbach’s alpha coefficients.ResultsThe final scale consists of 36 items with four domains: knowledge, attitude, practice, and skill. Exploratory factor analysis suggested four factors to explain 67.556% of the total variance (Kaiser–Meyer–Olkin test = 0.944, Bartlett’s test χ2 = 7384.296, P < 0.001). The results of confirmatory factor analysis showed that the model fits the data adequately. Cronbach’s coefficient was 0.945 for the overall scale, and for each domain, it was 0.952, 0.947, 0.908, and 0.923. The Spearman–Brown split-half reliability coefficient was 0.803 for the total scale, and for each domain, it was 0.925, 0.944, 0.901, and 0.917. The test–retest reliability coefficient of the total scale was 0.944, and for each domain of the scale, it was 0.865, 0.845, 0.987, and 0.936.ConclusionThe scale has acceptable content validity, construct validity, and good reliability. It can be used to evaluate the level of insulin medication literacy of patients with diabetes mellitus in China.